Inovação na atenção primária à saúde : um estudo de caso no município de Marau - RS - Silva, José Pretto da (My University, 2014)
Innovation and knowledge generation are objects of study on all economy areas, among them, health. This way, this mastering research searched to identify innovations on Health Primary Attention in the city of Marau-RS. To do so, a qualitative, exploratory, case study type survey was performed, applying as data collect instrument a semi structured interview with open and closed questions based on Oslo Manual (2004), reference of innovation of products and services, processes, marketing and management. A survey sample was formed by eight unit managers of Family Health Strategy (ESF) of the city cited above, as well as representatives of every department of central management of such structures. So, as final results it is possible to say the city has innovation on its public health system, but they are, however, just local innovations and it has reactive attitude, passive, regarding innovation. Among the innovations met on the city public health it is pointed innovations on marketing, such as Hepatitis B Vaccination Campaign; innovations on products and services, such as technological adaptation of municipal pharmacy to dispense basic, special and exceptional medicines and the promotion and adherence to programs such as Health at the Countryside and Health at the road; innovation on processes, such as the creation of Humanization Work Group and Family Health Support Center and Organizational or Management Innovations, pointing out city mapping due to elevated population growth and creation of ESFs coordinator post.
A inovação e a geração de conhecimento são objeto de estudo em todos os setores da economia, dentre estes, o da saúde. Neste sentido, esta dissertação de mestrado buscou identificar as inovações na Atenção Primária à Saúde no município de Marau-RS. Para tanto foi efetivada uma pesquisa de cunho qualitativo, exploratório, do tipo estudo de caso, aplicando-se como instrumento de coleta de dados uma entrevista semiestruturada, com perguntas abertas e fechadas baseadas no Manual de Oslo (2004), referência na inovação de produtos ou serviços, processos, marketingegestão. A amostra de pesquisa foi constituída por oito gestores das unidades de Estratégia de Saúde da Família (ESF) do referido município, bem como representantes de cada setor da gestão central das referidas estruturas. Sendo assim, tem-se como resultados finais que o município conta com a inovação em seu sistema de saúde pública, são, no entanto, apenas inovações locais e este tem uma atitude reativa, passiva, quanto à inovação.Dentre as inovações encontradas na saúde pública do município, destacamos as inovações em marketing, como a Campanha de Vacinação Hepatite B; as inovações em produtos e serviços, como a adequação tecnológica da farmácia municipal para a dispensação de medicamentos básicos, especiais e excepcionais e a promoção e adesão a programas como Saúde no Interior e Saúde na Estrada; inovações em processos, como a criação do Grupo de Trabalho de Humanização e o Núcleo de Apoio a Saúde da Família e Inovações Organizacional ou de Gestão, destacando o remapeamento do município em função do elevado crescimento populacional e a criação do cargo de coordenador dos ESFs.
Keywords: Saúde pública - Marau (RS); Serviços de saúde pública; Public health - Marau (RS); National health services